How to write a thesis protocol? - Amit Rastogi (Wolters Kluwer -Medknow Publications, 2023)
The thesis is the beginning of the research by any medical student. A thesis protocol is an important document that illustrates the plan and methodology for any research study. It serves as a template for the researcher and ensures that the study is done ethically and systematically. A systematically written protocol helps the researcher to plan, execute, and complete the study with reproducible results. Understanding all its components is essential for starting the research journey. A well-written thesis protocol must cover all essential aspects of study planning, including the study's objective, design, data collection tools, statistical analysis, and ethical procedures. This review article has been written by selecting and extracting data from online search engines such as Google and Bing and manual extraction of data from online articles available in PubMed and standard textbooks.